1980
DOI: 10.1038/bjc.1980.165
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of the cytostatic effect of adriamycin on drug concentration and exposure time in vitro

Abstract: Summary.-The surviving fraction (SF) of Chinese hamster cells and HeLa cells after treatment with a range of Adriamycin concentrations and exposure times was determined. The cytostatic effect was proportional to the product of extracellular drug concentration (c) and exposure time (t) according to the equation: SF=e-ktc. By determining the intracellular drug concentration at various exposures, it could be shown that absorbed dose is not proportional to exposure dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
26
0
1

Year Published

1981
1981
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(30 citation statements)
references
References 6 publications
3
26
0
1
Order By: Relevance
“…In a study of five patients with liver metastases from breast cancer and two patients with carcinoma of the bile duct, Garnick et al (1979) (Greene et al, 1983), the greater affinity of DOX for DNA as opposed to plasma (and, presumably, other extl r sites) ensues that the bulk of DOX will initially be found intacdllularly (Myers and Chabner, 1990 (Eichholtz-Wirth, 1980;Legha, 1982: Myers andChabner, 1990 Hepatic artery infusion with hepatic venous drug extraction, however, achieved these hepatic vein AUCs with 5.7-to 23-fold lower systemic exposure than observed during systemic DOX infusion. It is possible that this pharmacokinetic benefit may be exploited to take advantage of the doxorubicin therapeutic dose-response curve in the liver while avoiding increased systemic exposure.…”
Section: Resultsmentioning
confidence: 99%
“…In a study of five patients with liver metastases from breast cancer and two patients with carcinoma of the bile duct, Garnick et al (1979) (Greene et al, 1983), the greater affinity of DOX for DNA as opposed to plasma (and, presumably, other extl r sites) ensues that the bulk of DOX will initially be found intacdllularly (Myers and Chabner, 1990 (Eichholtz-Wirth, 1980;Legha, 1982: Myers andChabner, 1990 Hepatic artery infusion with hepatic venous drug extraction, however, achieved these hepatic vein AUCs with 5.7-to 23-fold lower systemic exposure than observed during systemic DOX infusion. It is possible that this pharmacokinetic benefit may be exploited to take advantage of the doxorubicin therapeutic dose-response curve in the liver while avoiding increased systemic exposure.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of ADR on Chinese cells depends not only on expos (Eichholtz-Wirth, 1980) but als4 density, pH and 02 tension. investigated dose and time ra survival depends exponentially dose, whereas intracellular drug uptake is a linear function.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, sampling points are generally chosen arbitrarily or sometimes by using more sophisticated approaches like sensitivity functions or stepwise linear regression (Ratain & Vogelzang, 1987). But these approaches are not optimal, since they do not provide maximal precision in model parameters.Adriamycin (ADM) is a broad-spectrum antineoplastic drug which is active against a wide variety of tumours.Experimental studies have suggested that ADM concentration-time product (area under the curve, AUC) is a determinant factor for tumour cell lethality (Eichholtz-Wirth, 1980; Ritch et al, 1982 Included were 42% of patients with primary tumour only, 10% with primary and distal metastases, 38% with multifocal metastases and 10% with isolated metastases (liver and bone). There was no concomitant irradiation.…”
mentioning
confidence: 99%
“…Experimental studies have suggested that ADM concentration-time product (area under the curve, AUC) is a determinant factor for tumour cell lethality (Eichholtz-Wirth, 1980; Ritch et al, 1982 Included were 42% of patients with primary tumour only, 10% with primary and distal metastases, 38% with multifocal metastases and 10% with isolated metastases (liver and bone). There was no concomitant irradiation.…”
mentioning
confidence: 99%
See 1 more Smart Citation